Detour - Ulmer, Edgar G. (Edgar George), 1904-1972; Neal, Tom, 1914-1972; Producers' Releasing Corporation; Cinetel Films ([Los Angeles, CA] : P.R.C. Productions., 1945)
In flashback, New York nightclub pianist Al Roberts hitchhikes to Hollywood to join his girl Sue. On a rainy night, the sleazy gambler he's riding with mysteriously dies; afraid of the police, Roberts takes the man's identity. But thanks to a blackmailing dame, Roberts' every move plunges him deeper into trouble... --
Tom Neal, Ann Savage, Claudia Drake, Edmund MacDonald, Tim Ryan, Esther Howard, Pat Gleason, Roger Clark.
Director of photography, Benjamin H. Kline; editor, George McGuire; music, Leo Erdody.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Hitchhiking -- Drama; San Francisco (Calif.) -- Drama; Murder -- Drama; Detective and mystery films; Film noir; Thrillers (Motion pictures); Feature films; Internet videos; Streaming video